ANTHROPOGENIC DETERMINANTS OF HYDROCHEMICAL INDICATORS DEGRADATION IN WATER BODIES - KIREITSEVA, HANNA; TSYHANENKO-DZIUBENKO, ILLIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article explores the main causes of anthropogenic water pollution and factors contributing to the exceedance of regulatory water quality indicators. The research systematically analyzes the complex interactions between human activities and water quality deterioration in natural water bodies. The study provides a comprehensive classification of pollution sources according to their impact on general sanitary and specific water quality indicators, which corresponds to the classification adopted in Ukrainian regulatory documents and the EU Water Framework Directive. The analysis reveals that industrial effluents, agricultural runoff, municipal wastewater, and urbanization processes are the primary contributors to water quality deterioration. Industrial pollution, particularly from metallurgical, chemical, and oil-refining industries, introduces toxic substances and heavy metals into water bodies. Agricultural activities contribute significant amounts of pesticides and fertilizers, leading to eutrophication and disruption of aquatic ecosystems. Improper treatment of municipal wastewater results in microbiological contamination and organic pollution. The research pays special attention to heavy metals and persistent organic pollutants, which pose the greatest threat to aquatic ecosystems and public health due to their high toxicity, bioaccumulation capacity, and persistence in the aquatic environment. The study establishes that most cases of water quality deterioration have complex nature, with simultaneous exceedance of both general sanitary and specific indicators, complicating the self-purification processes of water bodies. Based on the findings, the article substantiates the necessity of an integrated approach to solving water pollution problems, including the improvement of wastewater treatment technologies, strengthening control over industrial and agricultural discharges, developing sustainable water supply and sewerage infrastructure, and conducting regular water quality monitoring in accordance with national and EU requirements. The practical significance of the research lies in creating a methodological basis for targeted planning of water protection activities aimed at eliminating specific factors of water quality deterioration. The study also outlines prospects for further research, including the development of predictive models and innovative remediation methods.